CHRONIC INFLAMMATORY DEMYELINATING POLYRADICULONEUROPATHY CIDP - Ii Husein Barnedh* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INFLAMMATORY DEMYELINATING POLYRADICULONEUROPATHY CIDP IS CAUSED BY DAMAGE TO THE MYELIN SHEATH OF THE PERIPHERAL NERVE BY AUTOIMMUN ORIGIN BEFORE THE ERA OF MODERN ELECTRODIAGNOSTIC CIDP IS OFTEN CATEGORIZED AS CORTICOSTEROID RESPONSIVE POLYNEUROPATHY ON 1982 DYCK ET AL FINALLY INTRODUCE THE TERM CHRONIC INFLAMMATORY DEMYLINATING POLYRADICULONEUROPATHY